Identifying environmental sounds: a multimodal mapping study - Tomasino, Barbara; Canderan, Cinzia; Marin, Dario; Maieron, Marta; Gremese, Michele; D'Agostini, Serena; Fabbro, Franco; Skrap, Miran (Frontiers in Human Neuroscience, 2015)
Our environment is full of auditory events such as warnings or hazards, and their correct recognition is essential. We explored environmental sound (ES) recognition in a series of studies. In study 1 we performed an Activation Likelihood Estimation (ALE) meta-Analysis of neuroimaging studies addressing ES processing to delineate the network of areas consistently involved in ES processing. In study 2 we reported a series of 7 neurosurgical patients with lesions involving the areas found consistently activated by the ALE meta-analysis and tested their ES recognition abilities. In study 3 we investigated how the areas involved in ES might be functionally deregulated as an effect of lesion by performing an fMRI study on patients (in comparison to healthy controls). Areas found to be consistently activated in the ALE quantitative meta-analysis involved the STG/MTG, insula/rolandic operculum, parahippocampal gyrus and inferior frontal gyrus complex bilaterally. Some of these areas were found modulated by design choices, e.g., type of task, type of control condition, type of stimuli. Patients with lesions in these areas of the left and the right hemisphere had an impaired ES recognition. The most frequently lesioned area corresponded to the hippocampus/insula/superior temporal gyrus. For the most part, the patients’ responses were unrelated to the target sounds or were semantically related to the target sounds. The other type of responses were: auditorily related, semantically and auditorily related, and "I don't Know" answers. The fMRI evidenced deregulations of the activation reported in the right IFG and in the STG bilaterally and in the left insula. We showed that some of these clusters of activation truly reflect ES processing, whereas others are related to design choices. Our results allowed a parcelization of the activation found along the MTG/STG area